Environmental data exchange network for inland water - Haastrup, Palle; Würtz, Jørgen (Elsevier, 2007)
Understanding and protecting our environment is a key component of environmental development, yet access to a wide range of high-quality information is currently based on very limited data due to lack of the exchange of data between source and recipient. This three part book that first discusses the importance of data exchange and describes why it is essential for gathering data in the environmental sciences. Part Two takes the results of the Environmental Data Exchange Network for Inland Water project (EDEN-IW), and addresses its objectives for ensuring that the needs of citizens and enterprises of the environmental sciences community are met. Finally, Part Three takes a look at the wide variety of data policies and addresses how environment administrators in Europe can enhance their efficiency, openness and accountability. * Discusses the importance of data exchange, as well as database integration and distribution of data with software agents * Provides the results, objectives, and focus of the EDEN-IW project for sharing knowledge * Addresses current data exchange policies and its future impact within the environmental fields.